2017
DOI: 10.1111/hel.12413
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori, gastric cancer and other gastrointestinal malignancies

Abstract: In a retrospective study performed in California, U.S.A., ca. 3% of patients with gastric intestinal metaplasia (GIM) developed gastric cancer (GC) within a median time period of 4.6 years after diagnosis of GIM. This observation stresses the importance of targeted surveillance even in regions with a low GC prevalence. Patients with alcoholic liver disease as well as survivors of colorectal and lobular breast cancer were found to be at increased risk of secondary GC. A population-based Chinese study confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 25 publications
1
55
0
1
Order By: Relevance
“…Although the prevalence of H. pylori is declining in the United States and other Western countries, the incidence of esophageal adenocarcinoma, asthma, and allergies is on the rise. An increasing number of studies have suggested an inverse association between H. pylori and these diseases . Although a causal relationship has not been established, it is likely that the increase in these diseases can be attributed, in part, to the disappearance of H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of H. pylori is declining in the United States and other Western countries, the incidence of esophageal adenocarcinoma, asthma, and allergies is on the rise. An increasing number of studies have suggested an inverse association between H. pylori and these diseases . Although a causal relationship has not been established, it is likely that the increase in these diseases can be attributed, in part, to the disappearance of H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is a major factor in the development of stomach disorders and gastric cancer (GC) . Some reports have indicated a potential relationship between H. pylori infection and colorectal neoplasms; however, this has been disputed by others.…”
Section: Typical Microbial Families Contributing To Colorectal Cancermentioning
confidence: 99%
“…It is therefore possible that H. pylori , S. stercoralis or another unidentified mechanism was responsible for the colonic MALT lymphoma 35 . H. pylori , a known cause of gastric MALT lymphoma and gastric and colorectal adenocarcinomas, could have potentiated the development of colonic MALT lymphoma 36. However, this possibility is relatively unlikely because it is generally thought that extragastric MALT lymphomas are unrelated to H. pylori infection, but are rather being associated with other organisms that commonly colonise or infect the colon like S. stercoralis 6 29 37–40.…”
Section: Discussionmentioning
confidence: 99%